1992
DOI: 10.1093/nar/20.21.5519
|View full text |Cite
|
Sign up to set email alerts
|

Cloning by recognition site screening of two novel GT box binding proteins: a family of Sp1 related genes

Abstract: Previous analyses of the uteroglobin gene promoter revealed a GT1 box which is also found in the SV40 enhancer. The GT1 element in the context of the uteroglobin promoter is active in Ishikawa cells, a human endometrial cell line, but not in HeLa cells. Here we report the cloning by recognition site screening of two factors (SPR-1 and SPR-2) which bind to this GT1 motif. SPR-1 and SPR-2 are homologues of the transcription factor Sp1. All three proteins are closely related members of a gene family encoding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
446
1
7

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(476 citation statements)
references
References 40 publications
22
446
1
7
Order By: Relevance
“…This result is consistent with the observation that the recognition sequence for the members of the Sp family of transcription factors is highly variable, and it deviates¯exibly from the consensus Sp1 binding site (Kadonaga et al, 1986;Sa er et al, 1990). Unlike Sp1, Sp2 and Sp3 which are ubiquitously expressed in various tissues and cell types, Sp4 is known to be brain-speci®c (Kingsley and Winoto, 1991;Fischer et al, 1993;Hagen et al, 1992). Thus Sp4 may activate HGF expression in the central nervous system since the HGF gene is also expressed in this tissue (Jung et al, 1994).…”
Section: Discussionsupporting
confidence: 85%
“…This result is consistent with the observation that the recognition sequence for the members of the Sp family of transcription factors is highly variable, and it deviates¯exibly from the consensus Sp1 binding site (Kadonaga et al, 1986;Sa er et al, 1990). Unlike Sp1, Sp2 and Sp3 which are ubiquitously expressed in various tissues and cell types, Sp4 is known to be brain-speci®c (Kingsley and Winoto, 1991;Fischer et al, 1993;Hagen et al, 1992). Thus Sp4 may activate HGF expression in the central nervous system since the HGF gene is also expressed in this tissue (Jung et al, 1994).…”
Section: Discussionsupporting
confidence: 85%
“…We found that the human MIP gene sequence -253/+42 contains an active promoter in cultured lens cells but is inactive in non-lens cells (17). In the present study we have characterized a cis regulatory element required for MIP gene (18,19), is present in lens nuclear extracts and also interacts with this Sp1 binding site. Even though Sp1 is a ubiquitous factor, it regulates tissue-specific expression of a variety of genes (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 61%
“…We then decided to perform supershift assays to specifically identify which TF are producing the different retarded bands. We primarily used specific antibodies against the SP1 and SP3 TF, which are known to be able to bind with similar specificity and affinity to GC-boxes [24]. The results obtained are shown in Fig.…”
Section: Identification Of Tf By Supershift Analysismentioning
confidence: 99%